2018
DOI: 10.4067/s0717-73562018005000802
|View full text |Cite
|
Sign up to set email alerts
|

Estudio isotópico del consumo de recursos marítimos y terrestres en la prehistoria del desierto de Atacama

Abstract: Este trabajo explora desde una perspectiva diacrónica la dieta de las poblaciones prehispánicas de la región de Arica mediante análisis isotópicos de δ 13 C y δ 15 N, con el propósito de evaluar si hubo cambios en los patrones dietarios desde los primeros agricultores (periodo Formativo, 3500-1500 AP) hasta la ocupación Inka (periodo Tardío, 550-400 AP). En particular, examina el impacto del consumo del maíz en esta área, durante los periodos de mayor interacción social con los centros políticos del altiplano.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
1
0
2
Order By: Relevance
“…demonstrate that these millennia-old fishing, hunting, and gathering populations were born, and lived their daily lives. These result are consistent with δ 13 C and δ 15 N isotope values from other studies [70][71][72][73][74] that show principally a marine-based diet for coastal populations in the extreme north of Chile.…”
Section: Plos Onesupporting
confidence: 92%
“…demonstrate that these millennia-old fishing, hunting, and gathering populations were born, and lived their daily lives. These result are consistent with δ 13 C and δ 15 N isotope values from other studies [70][71][72][73][74] that show principally a marine-based diet for coastal populations in the extreme north of Chile.…”
Section: Plos Onesupporting
confidence: 92%
“…Experimental research has demonstrated that fertilization using bird guano and camelid dung can significantly increase nitrogen isotopic values in plant tissues (Szpak et al, 2012). Fertilizing crops with marine bird guano is a well-documented practice in many Andean coastal valleys during late Pre-Columbian and Colonial times (Hidalgo et al, 2019) and significantly high δ 15 N values have been reported in human, camelids, maize, macaws, and other animal and plant remains in sites such as Azapa 8, Camarones 8, Pica 8, and many more spread out throughout the Atacama Desert (King et al, 2018;Alfonso-Durruty et al, 2019;Capriles et al, 2021;Santana-Sagredo et al, 2021). Therefore, our isotopic results seem to verify the hypothesis that food crops were not only cultivated locally but also fertilized using bird guano (Szpak, 2014;Santana-Sagredo et al, 2021).…”
Section: Niche Construction and The Domestication Of The Desertmentioning
confidence: 99%
“…A fines de la década de los ochenta, estos fardos funerarios fueron abiertos y se realizaron autopsias a los cuerpos con el objetivo de analizar las enfermedades precolombinas, lo que se tradujo en publicaciones como el estudio de arsenicismo crónico (Figueroa et al 1988) y mal de Chagas (Aufderheide et al 2005). Los esqueletos de este sitio también han sido utilizados para otros estudios, como el de dieta (King et al 2018) cementerio de poblaciones foráneas (mitimaes). Señalan que al ser comunidades relocalizadas y no previamente expuestas al arsénico, la toxicidad del hidroarsenicismo habría afectado significativamente la salud y capacidad productiva de los individuos de CAM-9.…”
Section: Antecedentes Arqueológicosunclassified